Improvements to the DISA hydrosalinity model and its application to the Vaalharts Irrigation Scheme - Jonker, V.(Verno) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1995.